Recess and Reading Achievement of Early Childhood Students in Public Schools - Ümmühan Yeşil Dağlı (Arizona State University, 2012)
In recent years, schools have tended to eliminate recess period and to devote more time to instruction in order to increase academic achievement. Using a nationally representative sample, this study examined reading scores of students who experienced different numbers of recess days in a week, and different number of times and length of recess in a day. Students' gender, race, family socioeconomic status, initial reading scores, and age were controlled. Findings showed no significant main effects of recess; however, students who were exposed to a 16-30 minutes recess period tended to perform better. An interaction effect of race and the length of recess was found. It was concluded that recess does not have a significant effect on reading achievement. In other words, it does not improve or hurt academic achievement, but provides an opportunity for children to be physically active, play and socialize -- just to be a child.